2012
DOI: 10.1177/0300985812459337
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Lesions in Free-Ranging Black Caimans (Melanosuchus niger) Associated With Brevimulticaecum Species

Abstract: The stomachs of 100 free-ranging black caimans (Melanosuchus niger Spix, 1825) from the Mamirauá Sustainable Development Reserve, Amazonas state, Brazil, were examined for parasitism and pathologic lesions. All animals were harvested for human consumption. Ascaridoid nematodes were found in 67 caimans and were identified as Brevimulticaecum sp. These parasites were associated with focally extensive, chronic gastric ulcers and formation of localized intramural granulomas containing nematodes. All caiman were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Furthermore, the biological cycle of Brevimulticaecum sp. has not been completely elucidated, although general pathological aspects have been identified in other species (CARDOSO et al, 2012) leading us to suppose it is similar with regards to this nematode species. Nematodes cause infectious without apparent extensive pathological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the biological cycle of Brevimulticaecum sp. has not been completely elucidated, although general pathological aspects have been identified in other species (CARDOSO et al, 2012) leading us to suppose it is similar with regards to this nematode species. Nematodes cause infectious without apparent extensive pathological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that 67% of black caimans from the Mamirauá Development Reserve at the river Solimões, Amazonas state, had nematodes in the gastric mucosa and ulcers with hemorrhagic aspects. In some cases, there was even perforating ulcers in the serous layer of the stomach (Cardoso et al, 2013). This study shows the direct relation that exists among these microfilariae, which may affect the blood of M. niger from the middle Rio Negro.…”
mentioning
confidence: 61%
“…and Dujardinascaris sp. anisakids are associated with crocodyloids and alligatoroids as definitive hosts 31 , 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The egg wall, the circular shape (quasi-spherical), the smooth outer surface, and the diameter show similarities with the eggs of the Anisakis nematode-like Brevimulticaecum sp. 43 , 44 , Dujardinascaris sp. 31 , 44 , and Terranova sp 45 .…”
Section: Systematic Palaeontology and Descriptionsmentioning
confidence: 99%